2006
DOI: 10.1007/s10336-006-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variations of reproductive parameters in a booted eagle (Hieraaetus pennatus) population: the influence of density and laying date

Abstract: A population of booted eagles (Hieraaetus pennatus) consisting of 21-29 pairs was studied for 7 years (1998)(1999)(2000)(2001)(2002)(2003)(2004) in a forested mountainous region of southeastern Spain. The average egg-laying time was 25 April (earliest 31 March, latest 26 May). Sixty-eight percent of territorial pairs produced eggs, and 81% of reproductive pairs successfully raised at least one offspring. Mean clutch size was 1.91 eggs, and 84% hatched. The survival rate of chicks was high, with only 17% dying.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Dichlorodiphenyldichloroethylene residues also were higher in nonembryonated than in embryonated eggs in both goshawks and booted eagles, although only significantly so in the first species. In recent years, booted eagle and goshawk populations have decreased by approximately 30% and more than 50%, respectively, in the Murcia region [10]. Although OCs may affect reproductive success in some individuals, OC and PCB concentrations in booted eagle eggs have declined over the same period of time during which the populations have declined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichlorodiphenyldichloroethylene residues also were higher in nonembryonated than in embryonated eggs in both goshawks and booted eagles, although only significantly so in the first species. In recent years, booted eagle and goshawk populations have decreased by approximately 30% and more than 50%, respectively, in the Murcia region [10]. Although OCs may affect reproductive success in some individuals, OC and PCB concentrations in booted eagle eggs have declined over the same period of time during which the populations have declined.…”
Section: Resultsmentioning
confidence: 99%
“…Since 1991, goshawk ( Accipiter gentilis ) and booted eagle ( Hieraaetus pennatus ) populations have been declining in woodland areas of southeastern Spain, particularly in areas surrounded by agricultural zones that in the past have been treated with OC pesticides [10]. In the case of goshawks, the number of mating couples has dropped from 56 to 70 to a maximum of 20 today, whereas areas occupied by the booted eagle have dropped by 27.6% [10]. The overall aim of the present study was to examine whether OCs might be a causal factor in these declines.…”
Section: Introductionmentioning
confidence: 99%
“…The home range of this pair subsequently declined, and the young grew faster. In contrast, a study of Booted Eagles showed that breeding parameters were density independent (Martínez et al 2006). The occupancy rate of a nesting territory has been recently shown to be a consistent measure of territory quality in a wide range of species, including Black Kites (Milvus migrans) (reviewed by Sergio and Newton 2003;Sergio et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All three species show territorial behavior, nest in trees on large platforms and may alternate territories in different years (Pagán et al 2009). The booted eagle, a trans-Saharan migrant, the bulk of whose European population is located in the Iberian Peninsula, reaches a high population density in the study area (Martínez et al 2006b). In contrast, in the case of the buzzard and the goshawk, the study area represents the southernmost part of their distribution range (del Hoyo et al 1994).…”
Section: Introductionmentioning
confidence: 98%